#TITLE_ALTERNATIVE# - Hidayat Soesilohadi (NIM 311 98 003), RC
Abstract : Seasonal fluctuation of host plant (fruits) may act as an important limiting factor for fruit fly populations by its competition. In contrast, the competition may not be important in limiting fruit fly populations if the availability of fruit or food is abundant throughout the year. There are relationship between fruit fly population and its parasitoid population, and between fruit fly population and host fruit abundance. These phenomena indicate that both host plant and parasitoid affect fruit fly population. The extent to which host plant act as limiting factor and that of parasitoid as the regulator for fruit fly population are discussed in this dissertation. The objectives of the study are to identify the quality and quantity of star fruit, Averrhoa carambola as food resources to larvae and adult of fruit fly (Bactrocera carambolae) and to identify the role of major parasitoid as the regulator of fruit fly population. Star fruit quality was analysed by measuring of its protein and sugar content as well as pH. Quantity was identified by counting starfruit abundance in the orchard area located at IPPTP experimental garden, Subang. Counting of star fruit abundance and sampling of fruit from trees were conducted monthly over one year period from July 1999 to June 2000. To analyse fruit quality, a portion of fruits sampled was prepared for protein, sugar and pH analysis. While another portion was kept in the laboratory to observe the fruit fly and parasitoid data on the number of puparium and imago, longevity, male/female sex ratio and percentage of imago emergence. Temperature and rainfall at the orchard were measured from July 1999 to June 2000. The result of the study indicates that there were one species of fruit fly, Bactrocera carambolae Drew and Handcock and three species of its parasitoids, i.e., Biosteres vandenboschi Fullaway, Opius incisi Silvestri and one species from the Family of Eulophidae. The population of pupal parasitoid (B. vandenboschi) was dominant and higher than those of O. incisi and the eulophid throughout the year. The parasitism levels of B. vandenboschi, O. incisi and the eulophid against fruit fly pupa were ca 18.6 - 43.9%, 0 - 0.42% and 0 - 1.27% respectively over one year period from July 1999 to June 2000. Based on this finding, B. vandenboschi has proved to become as an important parasitoid which significantly regulates the fruit fly (B. carambolae) population. The puparium density fluctuated over one year period, and the fluctuation did not significantly relate to the number of star fruits in the field. The correlation between fruit fly population and star fruit abundance in the orchard was not also significant. This findings suggest that the fluctuation of fruit fly population were not affected by fruit abundance, because the fluctuation of star fruit abundance over the one year period may be still within the range of carrying capacity for the fruit fly. There were no significant correlations between the imago emergence with star fruit protein content with imago emergence and those with number of puparium. The correlation between star fruit protein content with female fruit fly longevity was significant. The correlations were positive which indicated that imago emergence, puparium number and female fruit fly longevity increased with star fruit protein content. There was not close relationship between fruit fly population and star fruit abundance, but it has a positive correlation. This indicates that the size of fruit fly population was limited by the numbers of star fruit and its population fluctuation was regulated by the parasitoid. The fluctuation in fruit fly population (B. carambolae) was always followed by the parasitoid population (B. vandernboschi). In addition, the population of fruit fly (t- generation) was positively correlated with local temperature during the study exposed to the former generation (t-1). Result of the study shows that the availability of star fruit may play as an important limiting factor for fruit fly population. The density-dependent relationship between fruit fly and its parasitoid resulted in their populations fluctuating around the equilibrium position. B. vandenboschi was a dominant parasitoid at the star fruit orchard in IPPTP Subang, and its become an important parasitoid in regulating the fruit fly (B. carambolae) population. The population dynamic of the parasitoid follows the population dynamic of its host (fruit fly). The fruit fly population significantly increased and followed the fluctuation of air temperature.